Body weight and socio-economic determinants: Quantile estimations from the British Household Panel Survey - Luca Pieroni; Luca Salmasi (University of Essex, Institute for Social and Economic Research (ISER), 2010)
This work examines the socio-economic determinants of body weight in UK by means of two recent waves from the British Household Panel Survey. Our results support some findings in the literature, but also point to new conclusions and show that quantile regression estimates are quite different from OLS ones. Among obese people, our results reveal that they are less so as male that do not spend extra-time at work or female increasing physical activity. Furthermore, smoking cessation may lead to moderate effects on weight increases only for underweight or normal-weight subjects but are not significant for obese ones.
Keywords: I10; I12; I18; 330; Body Mass Index; Overweight and Obesity; Quantile regression; Elasticity; Körpergewicht; Männer; Frauen; Sport; Rauchen; Großbritannien